2008
DOI: 10.1163/157075608x344640
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural relevance of AC and DC in prey detection by the brown bullhead, Ameiurus nebulosus

Abstract: A large range of aquatic vertebrates employs passive electroreception to detect the weak bioelectric fi elds that surround their prey. Bioelectric fi elds are dynamic in strength and frequency composition, but typically consist of a direct current (DC) and an alternating current (AC) component. We examined the biological relevance of these components for prey detection behaviour in the brown bullhead by means of a preference test. We gave each fi sh the choice between two small dipoles emitting a DC step or AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…We have little insight into the physiology of electroreception in toothed whales, but it is interesting that the ratio of detectability of DC and AC fields in dolphins is similar to that in elasmobranchs. Naturally occurring bioelectric fields can be described as dynamic electric fields consisting of a standing DC-dipole electric field modulated by low-frequency AC components arising, for example, from ion exchange processes and gill respiratory movements ( Bedore and Kajiura, 2013 ; Bodznick et al, 1992 ; Eeuwes et al, 2008 ; Haine et al, 2001 ; Kalmijn, 1972 , 1974 ; Wilkens and Hofmann, 2005 , 2008 ). Several studies have shown that sharks and rays respond best to DC electric field signals, but also to low-frequency AC potentials <20 Hz ( Eeuwes et al, 2008 ; Kalmijn, 1971 , 1974 ; Kimber et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have little insight into the physiology of electroreception in toothed whales, but it is interesting that the ratio of detectability of DC and AC fields in dolphins is similar to that in elasmobranchs. Naturally occurring bioelectric fields can be described as dynamic electric fields consisting of a standing DC-dipole electric field modulated by low-frequency AC components arising, for example, from ion exchange processes and gill respiratory movements ( Bedore and Kajiura, 2013 ; Bodznick et al, 1992 ; Eeuwes et al, 2008 ; Haine et al, 2001 ; Kalmijn, 1972 , 1974 ; Wilkens and Hofmann, 2005 , 2008 ). Several studies have shown that sharks and rays respond best to DC electric field signals, but also to low-frequency AC potentials <20 Hz ( Eeuwes et al, 2008 ; Kalmijn, 1971 , 1974 ; Kimber et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Naturally occurring bioelectric fields can be described as dynamic electric fields consisting of a standing DC-dipole electric field modulated by low-frequency AC components arising, for example, from ion exchange processes and gill respiratory movements ( Bedore and Kajiura, 2013 ; Bodznick et al, 1992 ; Eeuwes et al, 2008 ; Haine et al, 2001 ; Kalmijn, 1972 , 1974 ; Wilkens and Hofmann, 2005 , 2008 ). Several studies have shown that sharks and rays respond best to DC electric field signals, but also to low-frequency AC potentials <20 Hz ( Eeuwes et al, 2008 ; Kalmijn, 1971 , 1974 ; Kimber et al, 2011 ). Rays ( Raja clavata ) only showed good detection capabilities for AC fields of 16 and 32 Hz after increasing the electric field strength by factors of 8 and 32, respectively ( Kalmijn, 1974 ), whereas two shark species ( Scyliorhinus canicula and Triakis semifasciata ) no longer responded to AC stimuli with frequencies >16 Hz ( Kalmijn, 1973 , 1974 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation